Spatial-temporal evolution and peak prediction of embodied carbon emissions in China's interregional trade - Mo, Shu; Wang, Ting (Frontiers in Public Health, 2022)
The embodied carbon in inter-regional trade has a vital impact on the allocation of carbon emission reduction obligations and the formulation of carbon emission reduction strategies. Fewer studies have examined the spatial-temporal evolution pattern and peak prediction of embodied carbon emissions in China's inter-regional trade compared with the more numerous results on embodied carbon in international commerce. This paper applies the multi-regional input-output method to estimate the embodied carbon in inter-regional trade resulting from value-added transfer and investigates the spatial and temporal evolution of its patterns. The existence of an environmental Kuznets curve model with embodied carbon emissions as the index of environmental pollution in China is examined, and the time of the inflection point is calculated. The environmental Kuznets curve model is divided into four stages, and a two-dimensional model of economic development and embodied carbon emissions is proposed. The empirical findings indicate that the embodied carbon in China's interregional commerce has an overall rising tendency in the temporal dimension and a distribution characteristic of high in the west and north and low in the east and south in the spatial dimension. The Environmental Kuznets curve, which uses embodied carbon emissions as a measure of environmental pollution, has an inverse U-shaped and the time required to reach the inflection point varies by area. Economic development cannot be cross-stage but can shorten the duration of high carbon emissions. The government should promote the development of differentiated carbon emission reduction policies in each region, construct an inter-regional cooperative carbon emission reduction mechanism, encourage the low-carbon development of inter-regional trade, and realize the internal cycle of China's green economy. This study serves as a guide for the regions to establish scientific and acceptable carbon emission reduction strategies in order to achieve quality interregional trade development.